The Impact of Government Support on Innovations of Small and Medium Enterprises in Vietnam - Tuyen, Tran Quang; Huong, Vu Van (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
This is the first study to examine the impact of government support on the performance of small and medium enterprises (SMEs) in Vietnam. Using the data sets of the 2007-2015 period, the study indicates that government support has a positive impact on SMEs’ innovation, product innovation and application of new technologies. Our research also shows that government support affects the creativity, product and process innovation for formal enterprises only. The results imply that the government has significantly invested in supporting innovations. In order for these policies to be effective, it is vital to go along with other policies which in turn can promote the transition of SMEs from informal into formal firms.